Left atrial appendage occlusion in the absence of intraprocedural product specialist monitoring: is it time to proceed alone? Results from a multicenter real-world experience - Margonato, Davide; Rizza, Vincenzo; Ingallina, Giacomo; Preda, Alberto; Ancona, Francesco; Belli, Martina; Godino, Cosmo; Agricola, Eustachio; Della Bella, Paolo; Grasso, Carmelo; Contarini, Marco; Mazzone, Patrizio (Frontiers in Cardiovascular Medicine, 2023)
Background. Percutaneous left atrial appendage occlusion (LAAO) presents many technical complex features, and it is often performed under the intraprocedural surveillance of a product specialist (PS). Our aim is to assess whether LAAO is equally safe and effective when performed in in high-volume centers without PS support. Methods. Intraprocedural results and long-term outcome were retrospectively assessed in 247 patients underwent LAAO without intraprocedural PS monitoring between January 2013 and January 2022 at three different hospitals. This cohort was then matched to a population who underwent LAAO with PS surveillance. The primary end point was all-cause mortality at one year. The secondary end point was a composite of cardiovascular (CV) mortality plus non-fatal ischemic stroke occurrence at one year. Results. Of 247 study patients, procedural success was achieved in 243 patients (98.4%), with only one (0.4%) intraprocedural death. After matching, we didn’t identify any significant difference between the two groups in term of procedural time (70±19mins vs 81±30, p=0.106), procedural success (98.4% vs 96.7%, p=0.242) and procedure-related ischemic stroke (0.8% vs 1.2%, p=0.653). Compared to the matched cohort, a significant higher dosage of contrast was used during procedures without specialist supervision (98±19 vs 43±21, p<0.001), but this was not associated with a higher postprocedural AKI occurrence (0.8% vs 0.4%, p=0.56). At one year, the primary and the secondary endpoints occurred in 21 (9%) and 11 (4%) of our cohort, respectively. Kaplan Meyer curves showed no significant difference in both primary (p=0.85) and secondary (p=0.74) endpoints occurrence according to intraprocedural PS monitoring. Conclusions. Our results show that LAAO, despite the absence of intraprocedural PS monitoring, remains a long-term safe and effective procedure, when performed in high volume centers.